Staphylococcus aureus Colonization: Modulation of Host Immune Response and Impact on Human Vaccine Design - Brown, Aisling F.; Leech, John M.; Rogers, Thomas R.; McLoughlin, Rachel M. (Frontiers in Immunology, 2014)
In apparent contrast to its invasive potential Staphylococcus aureus colonizes the anterior nares of 20–80% of the human population. The relationship between host and microbe appears particularly individualized and colonization status seems somehow predetermined. After decolonization, persistent carriers often become re-colonized with their prior S. aureus strain, whereas non-carriers resist experimental colonization. Efforts to identify factors facilitating colonization have thus far largely focused on the microorganism rather than on the human host. The host responds to S. aureus nasal colonization via local expression of anti-microbial peptides, lipids, and cytokines. Interplay with the co-existing microbiota also influences colonization and immune regulation. Transient or persistent S. aureus colonization induces specific systemic immune responses. Humoral responses are the most studied of these and little is known of cellular responses induced by colonization. Intriguingly, colonized patients who develop bacteremia may have a lower S. aureus-attributable mortality than their non-colonized counterparts. This could imply a staphylococcal-specific immune “priming” or immunomodulation occurring as a consequence of colonization and impacting on the outcome of infection. This has yet to be fully explored. An effective vaccine remains elusive. Anti-S. aureus vaccine strategies may need to drive both humoral and cellular immune responses to confer efficient protection. Understanding the influence of colonization on adaptive response is essential to intelligent vaccine design, and may determine the efficacy of vaccine-mediated immunity. Clinical trials should consider colonization status and the resulting impact of this on individual patient responses. We urgently need an increased appreciation of colonization and its modulation of host immunity.